ИСЛАМИ ҚАРЖЫЛЫҚ ҚҰРАЛДАРДЫҢ ЕРЕКШЕЛІКТЕРІ МЕН ҚОЛДАНЫЛУ МҮМКІНДІКТЕРІ - Әбдімомынова, А Ш (Journal of Economic Research & Business Administration, 2015)
The article covers the basics of the functioning of Islamic financial system, methods and funding mechanisms to allow economic activities without violating the basic principles set out in the Shariah (Islamic law).